Maternal Interleukin-17 and disease activity influence pregnancy outcomes in women with psoriatic arthritis and ankylosing spondylitis - Ehab F. Girbash; Shaimaa M. Abdelwahab; Rehab M. Atef; Hala E. Sherif; Hussein M. Abdeldayem; Doaa S. Atta; Ahmed M. Radwan (BMC, 2023)
Abstract Objective We aimed in this study to evaluate the impact of maternal interleukin -17A and the activity of the illness on pregnancy outcomes in Psoriatic arthritis (PsA) and ankylosing spondylitis (AS) patients. Methods This prospective cohort research was carried out on 48 Psoriatic arthritis and ankylosing spondylitis pregnant women attending the inpatient and outpatient clinics of the Rheumatology & Rehabilitation and Obstetrics & Gynecology Departments, Faculty of Medicine, Zagazig University Hospitals in Egypt and 30 apparently healthy age- and sex-matched pregnant women between January 1,2018, and December 31, 2019. Results The study group patients had a higher risk of preterm labour (32-36 weeks gestation) (aRR 1.80, 95% CI 0.79-4.17), oligohydramnios (aRR 3.15, 95% CI 1.26-8.42), Caesarean delivery (aRR 1.57, 95% CI 1.41-2.68), and delivering infants small for gestational age (aRR 7.04, 95% CI 2.36-12.42). There was significant difference between the control group and the study groups regarding the level of IL-17A. Conclusion Many females with PsA and AS have uninhibited pregnancy with regard to adverse events, but in comparison with normal pregnancies particularly with high IL-17A during the third trimester we noticed a growing risk of preterm labour, oligohydramnios and cesarean section. Further studies are needed to evaluate high maternal IL-17A levels and fetal outcomes.